Tourniquets on Swedish merchant vessels - A review on the introduction of tourniquets onboard and the possible consequences - Holst, Samuel; Larsson, Erik (My University, 2022)
Tourniquets were introduced as a requirement in the medicine chest of Swedish merchant vessels in December of 2021. Responses to the proposition for the new medicine chest requirements questioned the tourniquet being added. This raised the question if the new requirement is based on science. The aim of the review was to investigate if bleeding control with tourniquets is possible onboard with regards to materials, drugs, and training. Factors for successful tourniquet use have been identified and compared to materials and competence available onboard. The possible educational and medical consequences have been evaluated. It has been found that materials, and in some cases, drugs relevant to tourniquet use are lacking. Competence in tourniquet use is not required in current regulation, which may now need to be revised. Several guidelines for tourniquet use exist, it is not known which is the most correct for use at sea. Two documents studied contained procedures for converting tourniquets, these were not consistent. The tourniquet may save lives, but the risk of complications may be unnecessarily great due to the lack of training in converting tourniquets to other means of bleeding control. There is a need for guidelines that are specifically designed for use at sea, according to which both the ship’s medicine chest and seafarer’s training should be adapted to.
Keywords: Tourniquet; haemorrhage; bleeding control; medicine chest; basic safety; medical care; TMAS